Influence of previous tuberculosis treatment on time to culture conversion for patients receiving a bedaquiline-containing regimen at Sizwe Tropical Disease Hospital, South Africa - Saimen, Amashnee (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.